Analisis Strategi Pengembangan Bisnis Agenda Apart sebagai Penyedia Layanan Penyewaan Apartement di Kota Bandung - Bagenda Aji; Muhammad Sugiharto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Apartment rental provider operating a lease arbitrage model in the Gateway Pasteur area of Bandung. A descriptive single-case study combining qualitative and quantitative approaches was employed using operational data from January–December 2025 and supporting secondary data. Business conditions were analyzed using STP, the 7P services marketing mix, and the Business Model Canvas, complemented by problem–solution fit, product–market fit, market sizing (TAM, SAM, SOM), and financial feasibility analysis (NPV, IRR, PI, Payback Period, and BEP). The findings indicate that Agenda Apart is positioned as an affordable and practical microstay service targeting young urban customers and transit travelers. Estimated market potential reached IDR 217.74 billion (TAM), IDR 21.77 billion (SAM), and IDR 229.80 million (SOM). Financial analysis confirms business feasibility, with a positive NPV of IDR 256.65 million, IRR of 134.98%, PI of 9.02, a payback period of 13.5 months, and a break-even point of 594 transactions annually. Strengthening digital marketing, operational standardization, and time-based pricing are recommended to improve capacity utilization.